Assessment of the Effect of Structural Modification of Ibuprofen on the Penetration of Ibuprofen from Pentravan® (Semisolid) Formulation Using Human Skin and a Transdermal Diffusion Test Model - Paula Ossowicz-Rupniewska (MDPI AG, 2021)
The effect of transdermal vehicle (Pentravan®) on skin permeability was examined for unmodified ibuprofen (IBU) and ion pairs of ibuprofen with new L-valine alkyl esters [ValOR][IBU]. The percutaneous permeation across the human skin and transdermal diffusion test model (Strat-M® membranes) of ibuprofen and its structural modification were measured and compared using Franz diffusion cells. For comparison, the penetration of ibuprofen from a commercial product was also investigated. The cumulative amount of drug permeated through human skin at the end of the 24 h study was highest for ibuprofen derivatives containing propyl (C3), isopropyl (C3), ethyl (C2), and butyl (C4) esters. For Strat-M®, the best results were obtained with the alkyl chain length of the ester from C2 to C5. The permeation profiles and parameters were appointed, such as steady-state flux, lag time, and permeability coefficient. It has been shown that L-valine alkyl ester ibuprofenates, with the propyl, butyl, and amyl chain, exhibit a higher permeation rate than ibuprofen. The diffusion parameters of analyzed drugs through human skin and Strat-M® were similar and with good correlation. The resulting Pentravan-based creams with ibuprofen in the form of an ionic pair represent a potential alternative to other forms of the drug-containing analgesics administered transdermally. Furthermore, the Strat-M® membranes can be used to assess the permeation of transdermal preparations containing anti-inflammatory drugs.